Dither removing of three-dimensional OCT retinal image - Wang, Pinghe (SPIE, 2020)
Optical coherence tomography (OCT) has been an important diagnosis tool for ophthalmic diseases because of its non-invasive and high-resolution feature. The image quality can effectively decrease because of the jitter from human body and eye, especially the distortion of the 3d reconstructed retinal images. A correction method for three-dimensional OCT retinal image based on curve fitting is proposed in this paper. The OCT retina image boundary is extracted and fitting by the preprocessing. Through frame sampling and curve fitting, the offset of each frame slice image is calculated. The experimental results show that the distortion of the OCT retina three-dimensional reconstruction image can be significantly corrected by the proposed method.